Protection of Women's Rights in terms of Legal Aspects - Fahruroji Fahruroji; Junifer Dame Panjaitan (Jurnal Restorasi : Hukum dan Politik, 2023)
Domestic violence is a criminal offense for which perpetrators can be punished. There are different types of domestic violence, including financial hardship. Because the perpetrator is still a partner, many victims are afraid to report their crimes to the police, and those closest to them are also afraid to help because it is considered not their duty. The problem of bullying in children at school is a serious and widespread problem. Bullying by friends has the potential to cause trauma to children so that it can inhibit their growth and development. It is aimed that by following this community service, individuals will be able to increase knowledge and actions in their households.